2021
DOI: 10.1001/jamanetworkopen.2021.22576
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Literacy Among Nulliparous Individuals and Maternal and Neonatal Outcomes

Abstract: IMPORTANCE Health literacy is considered an important social determinant of health that may underlie many health disparities, but it is unclear whether inadequate health literacy among pregnant individuals is associated with adverse maternal and neonatal outcomes.OBJECTIVE To assess the association between maternal health literacy and maternal and neonatal outcomes among nulliparous individuals. DESIGN, SETTING, AND PARTICIPANTSThis was a secondary analysis of a large, multicenter cohort study of 10 038 nullip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…health literacy interventions offer a way to improve outcomes for women's most at risk of health inequalities. This study is also in the same line with Nawabi, et al (2021) (48) who studied health literacy in pregnant women and showed that health literacy sensitive interventions during pregnancy is beneficial for all pregnant women regardless of their educational and health literacy levels. Moreover, the current study agrees with Berkman et al (2011) (49) who studied low health literacy and health outcomes: an updated systematic review and reported that Low health literacy is associated with poorer health outcomes and poorer use of health care services.…”
Section: Discussionsupporting
confidence: 89%
“…health literacy interventions offer a way to improve outcomes for women's most at risk of health inequalities. This study is also in the same line with Nawabi, et al (2021) (48) who studied health literacy in pregnant women and showed that health literacy sensitive interventions during pregnancy is beneficial for all pregnant women regardless of their educational and health literacy levels. Moreover, the current study agrees with Berkman et al (2011) (49) who studied low health literacy and health outcomes: an updated systematic review and reported that Low health literacy is associated with poorer health outcomes and poorer use of health care services.…”
Section: Discussionsupporting
confidence: 89%
“…We found that Flo helps women to be more knowledgeable about their cycle health, specifically, on how to manage menstrual symptoms, irregular cycle or related conditions, how to recognise cycle symptoms requiring medical attention as well as how their cycle affects their physical and mental health. Increasing women's knowledge in these areas might help to improve their quality of life as well as reduce financial costs related to the visits to the healthcare provider, over-the-counter drugs and medical or surgical treatment [69][70][71]. Furthermore, we found that of those respondents who fell pregnant, one in seven believe that Flo helped them to get pregnant.…”
Section: Knowledge and Health Improvements Among Flo App Usersmentioning
confidence: 77%
“…This is of particular importance as studies have shown that the prevalence of low levels of health literacy among pregnant women can reach up to 44% [26,30,[66][67][68]. Poor health literacy among pregnant women can result in an increased number of missed or later initiated prenatal care appointments, increased odds of not taking vitamin supplements during pregnancy [26,66], stronger beliefs of harms of medication or nonadherence to medications in pregnancy [67,68], and overall adverse maternal and neonatal outcomes [69]. Findings that Flo improves user knowledge on fertility and pregnancy health are not surprising as Flo app users track fertile days and ovulation with Flo to know where throughout the cycle they have higher chances to conceive.…”
Section: Knowledge and Health Improvements Among Flo App Usersmentioning
confidence: 99%
“…In our study cohort, women with mental disorders had low SES. Previous studies have shown controversial findings between low SES measured by income and educational attainment and the risk of preterm birth, low birth weight, and need for neonatal intensive care unit treatments ( 11 , 12 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 97%
“…There are conflicting results over the impact of maternal SES in pregnancy and outcomes. In many studies, there is heterogeneity of cohorts and the associations between variations remain unclear ( 11 , 21 , 22 ). In the study, the prevalence of GDM in this study was 16% as expected.…”
Section: Discussionmentioning
confidence: 99%